Cerebellar dysfunction in essential tremor. Issue 8 (8th April 2016) - Hanajima, Ritsuko; Tsutsumi, Ryosuke; Shirota, Yuichiro; Shimizu, Takahiro; Tanaka, Nobuyuki; Ugawa, Yoshikazu
ABSTRACT: Objectives: Few neurophysiological studies have investigated cerebellar function in patients with essential tremor, even though the cerebellum may contribute to tremor generation. Here, we studied cerebellar function in patients with essential tremor using 2 physiological methods. Methods: Participants were 20 patients with essential tremor and 30 age‐matched healthy volunteers, and the results were compared across the groups. We studied motor cortical inhibition using cerebellar magnetic stimulation and prism adaptation. Results: Both cerebellar inhibition and prism adaptation were affected in patients with essential tremor. The degree of tremor did not correlate with the degree of abnormality in either of the 2 experiments. Conclusions: The simplest explanation for the present results is that the cerebellum itself, including the Purkinje cells, is involved in essential tremor, which may reflect a primary pathogenic lesion or secondary compensatory physiological phenomenon to an original pathogenic lesion elsewhere. © 2016 International Parkinson and Movement Disorder Society